Prominin‐1 deletion results in spermatogenic impairment, sperm morphological defects, and infertility in mice - Haruka Matsukuma; Yuka Kobayashi; Shintaro Oka; Fumiaki Higashijima; Kazuhiro Kimura; Erika Yoshihara; Noriaki Sasai; Koji Shiraishi (Reproductive Medicine and Biology, 2023)
Abstract Purpose Spermatogenesis is a complex process orchestrated by several essential genes. Prominin‐1 (Prom1/PROM1) is a gene that is expressed in the testis but with a poorly understood role in spermatogenesis. Methods We used Prom1 knockout (Prom1 KO) mice to assess the role of Prom1 in spermatogenesis. To this end, we performed immunohistochemistry, immunofluorescence, western blotting, β‐galactosidase staining, and apoptosis assay. Additionally, we analyzed the morphology of sperm and assessed litter sizes. Results We observed that PROM1 is localized to the dividing spermatocytes in seminiferous epithelial cells, sperm, and columnar epithelium in the epididymis. In the Prom1 KO testis, an aberrant increase in apoptotic cells and a decrease in proliferating seminiferous epithelial cells were observed. Cellular FLICE‐like inhibitory protein (c‐FLIP) and extracellular signal‐regulated kinase 1/2 (ERK1/2) expression were also significantly decreased in Prom1 KO testis. In addition, a significantly increased number of epididymal spermatozoa with abnormal morphology and less motility was found in Prom1 KO mice. Conclusions PROM1 maintains spermatogenic cell proliferation and survival via c‐FLIP expression in the testis. It is also involved in sperm motility and fertilization potential. The mechanism underlying the effect of Prom1 on sperm morphology and motility remains to be identified.